Two new species of Xorides Latreille (Hymenoptera, Ichneumonidae) from China, with notes on biology and a key to species known from China - Sun, Shu-Ping; Lü, Jun; Broad, Gavin R.; Li, Tao; Sheng, Mao-Ling (European Journal of Taxonomy, 2023)
Two species of Xorides Latreille, 1809 are reported parasitizing wood-boring insects in trunks and relatively larger twigs of Juglans mandshurica Maxim. in Kuandian Manzu Autonomous County, Liaoning, in the Palaearctic part of China. Two new species are described: X. juglanse Sheng, Broad & Sun sp. nov. and X. kuandianense Sheng, Broad & Sun sp. nov. One species, X. sapporensis (Uchida, 1928), was associated with wood-borers in J. mandshurica Maxim. for the first time. A key to the 46 species of Xorides Latreille known from China is provided.